The study of dynamically active washing process of a washing machine - Heap, Yee Nean; Ryspek, Usubamatov, Prof. Dr.; Mohd Zaki, Ab Muin, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) organized by Universiti Malaysia Perlis (UniMAP), 8th - 10th March 2008 at Putra Palace, Perlis, Malaysia.